Species of Cixiidae and Issidae (Hemiptera: Auchenorrhyncha: Fulgoromorpha) Distributed in Sinop and Kastamonu (Turkey) - Rukiye Tanyeri; Ünal Zeybekoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, Cixiidae and Issidae (Hemiptera: Auchenorrhyncha) species collected from various localities in Sinop and Kastamonu between the years 2016-2018 were evaluated. 12 species belonging to 7 genera from Issidae and 4 species belonging to 4 genera from Cixiidae were determined. In addition, distributional data of the species in Turkey and in the world, and collection localities were given. Among the identified species, Kervillea placophora, Mycterodus confusus (Issidae) and Reptalus panzeri (Cixiidae) were recorded for the first time from the Black Sea Region of Turkey.